Analisis Efektivitas Penerapan Sistem Keuangan Desa (Siskeudes) Dalam Penyajian Laporan Keuangan Desa Liakutu - Maru, Maria Yasniana; Dekrita, Yosefina Andia; Patty, Thadeus Fransesco Quelmo (JFAS : Journal of Finance and Accounting Studies, 2026)
This study aims to analyze the effectiveness of the implementation of the Village Financial System (Siskeudes) in the presentation of village financial reports in Liakutu Village, Mego District, Sikka Regency. Siskeudes is an application developed by the Financial and Development Supervisory Agency (BPKP) and the Ministry of Home Affairs to assist in managing village finances, which includes planning, budgeting, implementation, and reporting. This study uses a qualitative method with data collection techniques in the form of structured interviews with informants consisting of the Village Treasurer, Village Head, Village Consultative Body (BPD), and the community. Data analysis was carried out using data analysis according to Miles & Huberman, which includes data reduction, data presentation, and conclusion. The Research results indicate that the implementation of Siskeudes in Liakutu Village has been effective, with success indicators including the suitability of information requested in the template/program, the appropriateness of report types, timeliness of reporting, conformity of procedures and reporting stages, as well as a feedback process conducted routinely every year. Nevertheless, there are some challenges regarding system updates that confuse the village treasurer. This study contributes to enhancing the understanding of the effectiveness of using Siskeudes as a transparent and accountable village accounting system.